Prevalence of congenital defects of heart and large vessels in adults - I.G. Lebid (Кардіохірургія та інтервенційна кардіологія)
This article provides the literature review including analysis and comparison of prevalence of congenital heart disease (CHD) and defects of large vessels in adults. There are 13 key publications on prevalence of congenital heart disease in adults (9 studies collected adult CHD cases from administrative governmental databases and 4 – reported calculation of survival related to the CHD birth prevalence). No country has comprehensive data regarding prevalence of CHD in adults. The number of patients is steadily increasing each year, further changing the structure of cardiovascular disease in adults. Available evidence suggests that the prevalence of CHD in adults is approximately 3.04 per 1000 adults. Extrapolating this data on population of Ukraine on January 1, 2016, excluding the temporarily occupied territory of the Autonomic Republic of Crimea, Sevastopol and the zone of antiterrorist operation, the number of adults with CHD may be about 105 thousands. Diagnosis of CHD in adulthood is often hidden under mask of other more common cardiovascular diseases. Complex and combined defects require permanent observation in the specialized cardiac centers.